Recent trends and advances in chloroplast engineering and transformation methods - Narra, Muralikrishna; Nakazato, Issei; Polley, Brittany; Arimura, Shin-ichi; Woronuk, Grant N.; Bhowmik, Pankaj K. (Frontiers in Plant Science, 2025)
Chloroplast transformation technology has become a powerful platform for generating plants that express foreign proteins of pharmaceutical and agricultural importance at high levels. Chloroplasts are often chosen as attractive targets for the introduction of new agronomic traits because they have their own genome and protein synthesis machinery. Certain valuable traits have been genetically engineered into plastid genomes to improve crop yield, nutritional quality, resistance to abiotic and biotic stresses, and the production of industrial enzymes and therapeutic proteins. Synthetic biology approaches aim to play an important role in expressing multiple genes through plastid engineering, without the risk of pleiotropic effects in transplastomic plants. Despite many promising laboratory-level successes, no transplastomic crop has been commercialized to date. This technology is mostly confined to model species in academic laboratories and needs to be expanded to other agronomically important crop species to capitalize on its significant commercial potential. However, in recent years, some transplastomic lines are progressing in field trials, offering hope that they will pass regulatory approval and enter the marketplace. This review provides a comprehensive summary of new and emerging technologies employed for plastid transformation and discusses key synthetic biology elements that are necessary for the construction of modern transformation vectors. It also focuses on various novel insights and challenges to overcome in chloroplast transformation.